Blood metal ion thresholds to identify patients with metal-on-metal hip implants at risk of adverse reactions to metal debris: An external multicenter validation study of Birmingham hip resurfacing and corail-pinnacle implants - Matharu, G; Berryman, F; Judge, A; Reito, A; McConnell, J; Lainiala, O; Young, S; Eskelinen, A; Pandit, H; Murray, D (Lippincott, Williams & Wilkins, 2017)
The authors of recent studies have reported newly devised implant-specific blood metal ion thresholds to predict adverse reactions to metal debris (ARMD) in patients who have undergone unilateral or bilateral metal-on-metal (MoM) hip arthroplasty. These thresholds were most effective for identifying patients at low risk of ARMD. We investigated whether these newly devised blood metal ion thresholds could effectively identify patients at risk of ARMD after MoM hip arthroplasty in an external cohort of patients.We performed a validation study involving 803 MoM hip arthroplasties (323 unilateral Birmingham Hip Resurfacing [BHR], 93 bilateral BHR, and 294 unilateral Corail-Pinnacle implants) performed in 710 patients at 3 European centers. All patients underwent whole-blood metal ion sampling, and were divided into 2 groups: those with ARMD (leading to revision or identified on imaging; n = 75) and those without ARMD (n = 635). Previously devised implant-specific blood metal ion thresholds (2.15 μg/L of cobalt for unilateral BHR; 5.5 μg/L for the maximum of either cobalt or chromium for bilateral BHR; and 3.57 μg/L of cobalt for unilateral Corail-Pinnacle implants) were applied to the validation cohort, and receiver operating characteristic curve analysis was used to establish the discriminatory characteristics of each threshold.The area under the curve, sensitivity, specificity, and positive and negative predictive values for the ability of each implant-specific threshold to distinguish between patients with and without ARMD were, respectively, 89.4% (95% confidence interval [CI] = 82.8% to 96.0%), 78.9%, 86.7%, 44.1%, and 96.9% for unilateral BHR; 89.2% (CI = 81.3% to 97.1%), 70.6%, 86.8%, 54.5%, and 93.0% for bilateral BHR; and 76.9% (CI = 63.9% to 90.0%), 65.0%, 85.4%, 24.5%, and 97.1% for unilateral Corail-Pinnacle implants. Using the implant-specific thresholds, we missed 20 patients with ARMD (2.8% of the patients in this series). We missed more patients with ARMD when we used the fixed thresholds proposed by regulatory authorities: 35 (4.9%) when we used the U.K. threshold of 7 μg/L for both cobalt and chromium (p = 0.0003), 21 (3.0%) when we used the U.S. threshold of 3 μg/L for both cobalt and chromium (p = 1.0), and 46 (6.5%) when we used the U.S. threshold of 10 μg/L for both cobalt and chromium (p < 0.0001).This external multicenter validation study confirmed that patients with blood metal ion levels below new implant-specific thresholds have a low risk of ARMD after MoM hip arthroplasty. Using these implant-specific thresholds, we missed fewer patients with ARMD compared with when the thresholds currently proposed by regulatory authorities were used. We therefore recommend using implant-specific blood metal ion thresholds when managing patients who have undergone MoM hip arthroplasty.Diagnostic Level III. See Instructions for Authors for a complete description of levels of evidence.